Clinical importance of extended-spectrum beta-lactamase (PER-1-type)-producing Acinetobacter spp. and Pseudomonas aeruginosa strains - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2001)
Recently, an extended-spectrum beta -lactamase (PER-I) was found to be disseminated among Acinetobacter spp, and Pseudomonas aeruginosa isolates in Turkey. A population-based cohort study was conducted to elucidate predictive mortality factors in patients with nosocomial infections caused by Acinetobacter spp. and P. aeruginosa, with particular reference to PER-1-type extended-spectrum beta -lactamase (ESBL) production. The study group comprised 16 and 21 non-survivors and 82 and 126 survivors in cohorts infected with Acinetobacter and E. aeruginosa, respectively. In the Acinetobacter-infected cohort, nosocomial pneumonia, hypotension and infection with a PER-positive isolate were independent predictors of mortality. In the P. aeruginosa-infected cohort, impaired consciousness, a PER-positive isolate, male sex and (with a negative relative risk) urinary tract infection were independent predictors of death. This study demonstrated the relationship of PER-1-type ESBL-producing Acinetobacter spp. and P. aeruginosa with poor clinical outcome.
Keywords: OUTER-MEMBRANE; RESISTANCE; BAUMANNII; ACQUISITION; PNEUMONIA; MORTALITY; OUTBREAK